2009
DOI: 10.1021/jf8037456
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Selected South African Young Cultivar Wines Using FTMIR Spectroscopy, Gas Chromatography, and Multivariate Data Analysis

Abstract: The powerful combination of analytical chemistry and chemometrics and its application to wine analysis provide a way to gain knowledge and insight into the inherent chemical composition of wine and to objectively distinguish between wines. Extensive research programs are focused on the chemical characterization of wine to establish industry benchmarks and authentication systems. The aim of this study was to investigate the volatile composition and mid-infrared spectroscopic profiles of South African young cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 24 publications
0
55
1
1
Order By: Relevance
“…Determination of the standard parameters of the juice and wine were performed with a WineScan FT120 spectrophotometer (FOSS Analytical, Denmark) (according to the method described by Louw et al, 2009). Duplicate scans were obtained for each sample.…”
Section: Standard Wine Analysismentioning
confidence: 99%
“…Determination of the standard parameters of the juice and wine were performed with a WineScan FT120 spectrophotometer (FOSS Analytical, Denmark) (according to the method described by Louw et al, 2009). Duplicate scans were obtained for each sample.…”
Section: Standard Wine Analysismentioning
confidence: 99%
“…After each sample run, a post run of 5 minutes at oven temperature 240°C, with a column flow of 6 mL/minute cleaned the column from high boiling contaminants. The GC-FID method described above, including the sample preparation procedure, has been validated (Louw, 2007) and applied in a previous study (Louw et al, 2009). The limits of detection (LOD) and quantification (LOQ) for the analytes are shown in Table 2.…”
Section: Gas Chromatographic Conditionsmentioning
confidence: 99%
“…It is well known that compounds other than alcohols, esters and fatty acids contribute to unique cultivar characteristics and may therefore contribute to a stronger classification model. Indeed, in a recent paper (Louw et al, 2009), it was found that discriminant models using fermentation volatiles improved when used in conjunction with infrared spectral data of the wines under investigation. Spectral data, being of highly multivariate nature, provide a wealth of non-specific compositional information and can be useful to provide complementary data for targeted analytical methods such as the GC-FID analysis used in this study (Skov et al, 2008).…”
Section: Tablementioning
confidence: 99%
“…The complexity of smells varies: floral odors can contain dozens of odor components (Raguso, 2008), while more complex smells such as wines and coffees are composed of hundreds (Louw et al, 2009). However, it seems that many complex smells can actually be reduced to the impact of a few molecules (e.g.…”
Section: The Stimulusmentioning
confidence: 99%